Handbook of 5G Wireless Networks - Musk, Alexander (United States : States Academic Press, 2021)
5G wireless networks are a fifth generation technology standard for broadband cellular networks, deployed by cellular phone companies worldwide. It is the successor of 4G networks. The service area of these networks is divided into small geographical areas called cells. 5G wireless devices in a cell are connected to the internet and telephone network by radio waves through a local antenna in the cell. 5G networks have greater bandwidths compared to the previous networks, and will provide higher download speeds. It is also expected to be used as general internet service providers for laptops and desktops, and aid the advancement of the Internet of things technology. This book brings forth some of the most innovative concepts and elucidates the unexplored aspects of 5G wireless networks. It aims to present researches that have transformed this area of study and aided its advancement. This book will prove to be immensely beneficial to students and researchers in this field.
Includes index.
Includes bibliographical references.
Keywords: Application software; Computer communication systems; Mobile communication systems; Power electronics; Wireless communication systems